Price and e-service quality effects on Gen Z customer loyalty: The mediating role of customer satisfaction in Smartfren internet service provider - Putri, Kartika Amalia; Thaib, Ilham (Marketing Management Studies, 2025)
Indonesian Internet Service Providers like Smartfren offer diverse internet package options, addressing the changing lifestyles and consumer preferences of Gen Z in the digital era. The research investigates the impact of price and e-service quality on customer loyalty among Gen Z in Padang City, with customer satisfaction as a mediator. This type of research is descriptive with quantitative methods and the sampling method uses nonprobability sampling type purposive sampling. This descriptive, quantitative research used 155 respondents, collected via Google Form, and processed using Partial Least Squared-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The study reveals that 1) Price and E-Service Quality have a positive but not significant effect on Customer Loyalty 2) Price and E-Service Quality have a positive and significant effect on Customer Satisfaction 3) Customer Satisfaction has a positive and significant effect on Customer Loyalty 4) Price and E-Service Quality have a positive and significant effect on Customer Loyalty through Customer Satisfaction